Morphology of the immature female stages and the wax test of ten species of Ceroplastes (Hemiptera: Coccomorpha: Coccidae: Ceroplastinae) from Brazil - Rosa, Keila C. C.; Peronti, Ana L. B. G. [UNESP]; Hodgson, Chris J.; Sousa-Silva, Carlos R. (Magnolia Press, 2016)
This paper describes the development of the waxy test and the microscopic characters of the three female nymphal instars of Ceroplastes cirripediformis Comstock, C. diospyros Hempel, C. floridensis Comstock, C. flosculoides Matile-Ferrero, C. formicarius Hempel, C. formosus Hempel, C. grandis Hempel, C. iheringi Cockerell, C. lucidus Hempel, and C. stel-lifer (Westwood). The discussion compares their morphology and divides the species into three groups according to the pattern of their dermal and wax characters.
Keywords: Female nymphs; Morphology; Soft scale; Taxonomy; Wax scale